Efektivitas Penggunaan Media Pembelajaran Berbasis Quizizz dalam Meningkatkan Motivasi Belajar Siswa Kelas VI di SDN Ngesrep 03 Semarang - Vanka Septalianto; Arsito Ari Kuncoro; Unang Achlison (CV. ALIM'SPUBLISHING, 2026)
The rapid development of information technology has transformed conventional learning into interactive digital learning. One of the most widely used learning platforms is Quizizz, a game-based learning application that provides interactive quizzes, leaderboards, automatic scoring, and instant feedback. This study aims to analyze the effectiveness of Quizizz-based learning media in improving the learning motivation of sixth-grade students at SDN Ngesrep 03 Semarang. This study employed a quantitative approach using a quasi-experimental pretest-posttest design. The participants were sixth-grade students who participated in classroom learning using Quizizz. Data were collected through learning motivation questionnaires, classroom observations, documentation, and learning achievement results. Descriptive statistical analysis was applied to examine changes in students' learning motivation before and after implementing Quizizz. The findings indicate that Quizizz significantly improves students' learning motivation. Improvements were observed in learning enthusiasm, classroom participation, attention to learning materials, confidence in answering questions, and willingness to achieve better academic performance. Furthermore, the gamification features of Quizizz created a more enjoyable learning environment that encouraged students to participate actively throughout the learning process. This study concludes that Quizizz is an effective digital learning medium for improving elementary students' learning motivation and can be implemented as an innovative instructional and assessment tool.